Role of Ministerial Media Arms During COVID-19 In Malaysia - Ahmed Badawy; Mohammed A. Gharawi; Azman Bidin; Mutasim Khamis (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2020)
Introduction: The recent outbreak of novel corona virus known as COVID-19, has caused over 556.335 deaths, left more than 12 million infected people worldwide by 11th of July 2020 (Organization, 2020a), in addition to global negative impact on nearly most life sectors. Media played -and still- a vital role in the containment of this global health threat by spreading the essential knowledge and awareness between people. Comparing to its neighbours, Malaysia seems to have good score in the battle of COVID-19. With 8,815 confirmed cases, 8,562 total discharged cases and 123 deaths by 21th of July 2020 (Malaysia, 2020), it was interesting to study the role of media in shaping people’s awareness during the current global crisis to face the danger of such virus on the national level. Aim: To analyse and understand the Malaysian government role in shaping people’s awareness toward COVID-19. Method: Authors are tracking and analysing the ministerial media arms role in handling the situation, based on the official data and statements released by the national news agency, Bernama. This article is divided into three main parts as it discusses the role of three specific governmental official; Prime Minister, General Director of Ministry of Health, and Senior Security Minister, Findings: The Malaysian governmental officials namely Prime Minister, General Director of Ministry of Health, and Senior Security Minister followed a successful strategy during COVID-19 pandemic to rely a part on people’s awareness by providing them with the accurate information to avoid the viral spread of fake news. Conclusion: Malaysia was able to contain the pandemic on the national level powered by people’s awareness.